A Treasury of Christmas stories - Hardy, Sian.; Aldous, Kate (New York : Kingfisher Books, 1994)
"A collection of Christmas stories by such authors as Carolyn Haywood, Joan Aiken, and Roger Duvoisin."
Keywords: Christmas stories; Children's stories; Christmas -- Fiction; Short stories